Afrocentric epistemic systems and higher education curriculum. The Case of a university in Zimbabwe - Murwira, S.; Higgs, P. (South African Journal of Higher Education, 2023)
African Afrocentric epistemic systems have impacted upon the existence and practices of African communities throughout the ages. These epistemic systems have influenced the enactment of how Africans have lived in their communities and how they have sustained and used their resources. However, these epistemic systems encountered an existential problem in the promulgation of Eurocentric epistemic systems which marginalized the significance and centrality of Afrocentric epistemic systems in Zimbabwe’s higher education curriculum. This article concerns itself specifically with the higher education curriculum in Zimbabwe in terms of an Afrocentric perspective and investigates ways in which lecturers’ and students’ perceptions towards Afrocentric epistemic systems can be changed considering the problem of the colonization of the Zimbabwe’s higher education curriculum by Eurocentric epistemic systems. This article, therefore, argues for the incorporation of Afrocentric epistemic systems in bringing about a distinctly Afrocentric perspective in the curriculum, the case of a University in Zimbabwe.